Biochemical conversion of Brassicacarinata biomass to organic acids. Issue 4 (16th February 2021) - Ammar, Ehab M.; Martin, Jessica; Philippidis, George P.
Abstract: The economics of the inedible oilseed crop Brassica carinata as a source of renewable fuels can be enhanced by converting its cellulosic biomass to value‐added chemicals, such as organic acids. We investigated the biochemical conversion of carinata biomass to propionic acid by first pretreating the carinata meal (CM), which is obtained after extraction of the oil from carinata seeds, with concentrated phosphoric acid to remove hemicellulose and gain access to the cellulose constituent of the meal. We then subjected the pretreated meal to enzymatic hydrolysis with cellulase enzyme to depolymerize cellulose to glucose. The overall conversion of carinata cellulose to glucose was 85%, which is promising. Finally, the recovered glucose was successfully fermented primarily to propionic acid using the bacterium Propionibacterium freudenreichii with a yield of 0.57 g of produced propionic acid per gram of consumed cellulosic glucose. The biobased propionic acid and other co‐produced organic acids can serve as renewable building blocks for manufacturing industrial chemicals and food preservatives replacing fossil‐derived organic acids. Hence, CM constitutes a renewable source of fermentable carbohydrates potentially improving the economics and sustainability of the carinata value chain. Abstract : Brassica carinata, an inedible oilseed crop that can be cultivated by farmers as a winter cover crop in the southeastern United States, is viewed as a sustainable source of renewable aviation fuel and other products. To enhance the economics of carinata, we investigated the conversion of the seed fiber (biomass) to propionic acid after extraction of the oil. Using phosphoric acid and cellulase enzyme, we successfully produced propionic acid using the bacterium Propionibacterium freudenreichii . Carinata‐based propionic acid can serve as renewable feedstock for manufacturing chemicals and food preservatives, while improving the economics and sustainability of the carinata value chain.